The Effect of Nursing Students' Self-Efficacy on Patient-Centered Communication During the COVID-19 Pandemic: The Mediating Effect of Learning Burnout - Jing Wang (Frontiers Media S.A., 2021)
Background: The 2019 coronavirus disease (COVID-19) outbreak has put the global health system under the spotlight. As part of the medical workforce, nurses play an important role in interacting with and caring for patients; hence, patient-centered communication (PCC) has been emphasized in nursing education. Thus, it is worth investigating how future nurses perceive PCC and PCC-related factors under the special circumstances of COVID-19. For this purpose, the present study analyzed the mechanisms underlying the association between self-efficacy and nurse–patient communication tendency through learning burnout among nursing students during the COVID-19 pandemic.Methods: The general self-efficacy questionnaire, college students' learning burnout scale, and doctor–patient communication tendency scale were used to survey 2,231 nursing students in higher vocational medical colleges at the onset of the COVID-19 pandemic.Results: General self-efficacy can directly negatively correlate with the degree of nursing students' overall nurse–patient communication, including caring, sharing, and health promotion. Dejection from learning burnout partially mediated the relationships between self-efficacy and caring and between self-efficacy and sharing; it fully mediated the relationship between self-efficacy and health promotion. Reduced personal accomplishment partially mediated between self-efficacy and caring, while it fully mediated between self-efficacy and health promotion; however, it did not play a role in the sharing model.Conclusion: Self-efficacy influences nurse–patient communication through learning burnout. Specifically, dejection and reduced personal accomplishment—two aspects of learning burnout—may compromise nursing students' willingness to engage in PCC. Thus, the importance of PCC, especially during critical health situations such as pandemics, should be emphasized further in future nursing education.